因式分解:(X-1)(X-2)(X-3)(X-4)-120(x-1)(x-2)(x-3)(x-4)-120
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 08:15:49
因式分解:(X-1)(X-2)(X-3)(X-4)-120(x-1)(x-2)(x-3)(x-4)-120因式分解:(X-1)(X-2)(X-3)(X-4)-120(x-1)(x-2)(x-3)(x-
因式分解:(X-1)(X-2)(X-3)(X-4)-120(x-1)(x-2)(x-3)(x-4)-120
因式分解:(X-1)(X-2)(X-3)(X-4)-120
(x-1)(x-2)(x-3)(x-4)-120
因式分解:(X-1)(X-2)(X-3)(X-4)-120(x-1)(x-2)(x-3)(x-4)-120
=[(X-1)(X-4)][(X-2)(X-3)]-120
=[(X²-5X)+4][(X²-5X)+6]-120
=(X²-5X)²+10(X²-5X)+24-120
=(X²-5X)²+10(X²-5X)-96
=(X²-5X-6)(X²-5X+16)
=(X-6)(X+1)(X²-5X+16)
http://zhidao.baidu.com/question/19114293.html?si=2
请参考,大有收获
(x-1)(x-2)(x-3)(x-4)-120
=[(x-1)(x-4)][(x-2)(x-3)]-120
=[(x^2-5x)+4][(x^2-5x)+6]-120
=[x^2-5x]^2+10[x^2-5x]+24-120
=[x^2-5x]^2+10[x^2-5x]-96
=[x^2-5x+16][x^2-5x-6]
=[x^2-5x+16][x-6][x+1]
两项两项来,(x-1)(x-4)=x^2-5x+4,(x-2)(x-3)=x^2-5x+6,原式即为(x^2-5x+4)*(x^2-5x+6)-120=(x^2-5x)^2+10(x^2-5x)-96=(x^2-5x+16)*(x^2-5x-6)=(x^2-5x+16)*(x+1)*(x-6)
(x^3-x^2)+(x-1)因式分解
因式分解:(x+1)(x+2)(x+3)(x+4)+1
因式分解:x^4+x^3-2x^2-x+1
(x-1)(x-2)(x-3)(x-4)-24 因式分解
(x+1)(x+2)(x+3)(x+4)-24因式分解
x^4+x^3-4x^2+x+1因式分解
因式分解(x+1)(x+2)(x+3)(x+4)-24
因式分解(x-1)(x+2)(x+3)(x+6)-13
因式分解(X+1)(X+2)(X+3)(X+4)-120
因式分解(x+1)(x-2)(x-3)(x-6)+20
因式分解(x+1)(x+2)(x+3)(x+4)-120
因式分解1+x+x^2+x^3+```+x^15
因式分解 (x-1)(x+2)(x-3)(x+4)-144
(x+1)(X+2)(x+3)(x+4)-120 因式分解(x+1)(X+2)(x+3)(x+4)-120因式分解
因式分解3x^2-2x-1
因式分解x^3-2x^2+1
x^2+3x-1如何因式分解
X^4-3x^2+1 因式分解